The Right to Disconnect: Influence on Competitiveness, Productivity and Creativity - Varela-Castro, Werner Horacio; Briceño-Santacruz, María de los Angeles; Castro-Solano, María Olivia (Mercados y Negocios, 2022)
This research aims to determine which variables and factors are obtained as benefits or advantages of the observance of the right to disconnect law and whether it will influence labor and educational competitiveness. Initially, existing literature was reviewed, and an own elaboration instrument was applied to 73 sample subjects. The found result was the need for recognition and awareness of organizations to respect the obligation of the right to disconnect to generate work and academic independence of workers, teachers, and students to take advantage of the free time of these people in order to improve their social relationships and strengthen their knowledge to perfect their work and increase their job and educational competitiveness.